The Development of an Ultrasonic Degassing Process for Aluminium Casting. (2019) - Rundquist, V.; Paci, M.; von Gal, R.
Abstract: The SCR Technologies group of Southwire Company, LLC has recently introduced the Ultra-D™ Degasser to the aluminium industry. Ultrasonic energy is used to reduce dissolved hydrogen, alkali metals and other harmful inclusions from molten aluminium without the use of corrosive chemicals such as chlorine. This paper will briefly review the development cycle and implementation of the technology in Twin Roll Casting. Next, operational data from Profilglass will be summarized and discussed. Further, we will advance the view that using the Ultra-D TM degasser in strip casting could potentially reduce the usage of grain refiners by as much as 66% when compared to existing degassing technologies